Nanomaterial-Mediated Stem Cells Fate Regulation: From Mechanism of Action to Regenerative Medicine Applications - Xuetong Wang; Yiming Sun; Ping Zhang; Huan Zhou; Lei Yang (Cytotherapy and Longevity, 2026)
Stem cells possess self-renewal capacity and differentiation potential. Under appropriate conditions, they can continuously divide to generate more stem cells of the same type or differentiate into various specialized cell types, thereby contributing to the formation of diverse tissues and organs. In tissue engineering and regenerative medicine, stem cells serve as key elements for repairing or replacing functional tissues lost due to disease, injury, or aging. The development of nanomaterials has provided new tools and approaches for stem cell research, particularly in the biomedical field, where they are widely applied in drug delivery, biosensing, medical imaging, and tissue engineering. Moreover, through interactions with cell membranes and/or intracellular components, nanomaterials can modulate key stem cell functions — including differentiation, proliferation, and adhesion — thereby enhancing the therapeutic efficacy of stem cells in biomedical applications. This review first introduces the main characteristics and potential risks associated with the application of nanomaterials to stem cells. The subsequent section provides an overview of how nanomaterials regulate stem cell biological functions and activate associated signaling pathways, followed by a discussion of future directions and challenges in this field.